2018
DOI: 10.1155/2018/7535417
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Imazethapyr Surface Molecularly Imprinted Polymers for Its Selective Recognition of Imazethapyr in Soil Samples

Abstract: A novel strategy based on imazethapyr (IM) molecular-imprinting polymers (MIPs) grafted onto the surface of chloromethylation polystyrene resin via surface-initiated atom transfer radical polymerization (SI-ATRP) for specific recognition and sensitive determination of trace imazethapyr in soil samples was developed. The SI-ATRP was performed by using methanol-water (4 : 1, v/v) as the solvent, acrylamide as the functional monomer, trimethylolpropane trimethacrylate (TRIM) as the cross-linker, imazethapyr as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…MIPs are synthetic polymers with high molecular recognition capacity through a mechanism similar to an enzyme-substrate complex, in which the template is recognized by the selective cavities of the material by interactions with its functional monomers, allowing them to be applied in extraction methods and determination of compounds of environmental interest, such as pesticides and organic pollutants [24,25]. Studies applying MIPs in solid-phase extraction (SPE) procedures have been reported for imidazolinone herbicides determination in food samples [26][27][28]. However, to the best of our knowledge, there are no applications of MIPs for electroanalytical determinations of IMT.…”
Section: Introductionmentioning
confidence: 99%
“…MIPs are synthetic polymers with high molecular recognition capacity through a mechanism similar to an enzyme-substrate complex, in which the template is recognized by the selective cavities of the material by interactions with its functional monomers, allowing them to be applied in extraction methods and determination of compounds of environmental interest, such as pesticides and organic pollutants [24,25]. Studies applying MIPs in solid-phase extraction (SPE) procedures have been reported for imidazolinone herbicides determination in food samples [26][27][28]. However, to the best of our knowledge, there are no applications of MIPs for electroanalytical determinations of IMT.…”
Section: Introductionmentioning
confidence: 99%